Hope amid uncertainty : exploring the validity of the State Hope Scale in post-migration adult language learning - Thorsen, Cecilia; Henry, Alastair (Journal of Multilingual and Multicultural Development, 2025)
When language learning takes place post-migration, the challenge is not only to attain fluency. Learning is tied up with life opportunities and is overshadowed by hopes and fears for the future. In the post-migration phase, hopeful thinking can support the acculturation process. Hope is a goal-related construct that captures variation in adaptability in the pursuit of positive outcomes. It involves the interaction of (a) agency (goal-directed energy) and (b) pathways (strategic planning for goal accomplishment). When language learning takes place in situations of uncertainty, Hope can provide insights into adaptive learning behaviour. The purpose of the study was to examine the psychometric properties of the State Hope Scale (SHS) in a sample of adult migrants (n = 211) learning Swedish. First, the factor structure of Hope was investigated using confirmatory factor analysis (CFA). Second, convergent and discriminant validity were examined in relation to the associable constructs of Grit and Academic Buoyancy. Finally, measurement invariance for gender was examined. Findings support a one-factor structure. Consideration is given to (a) psychometric qualities of the SHS, and (b) the role of Hope in L2 psychology. Since language learning always involves a degree of uncertainty, Hope can be a useful construct for studying learner psychology.
Keywords: Hope; L2 motivation; migration; motivation of uncertainty; State Hope Scale; validity